Formação continuada de professoras da Educação Infantil em Goiás: concepções e perspectivas - Santos , Cristiane Riberio dos (2022)
This research was developed in the Graduate Program in Education (PPGE) at the Faculty of Education (FE) of the Federal University of Goiás (UFG), in the line of research “Teaching Professional, Training and Educational Practices”, and is one of the actions of the project “Public policies and childhood education in Goiás: history, conceptions, projects and practices”, linked to the Center for Studies and Research on Childhood and its Education in Different Contexts (NEPIEC). The investigation arose from the interest of identifying which are the continuous or non-continuous training processes experienced by Childhood Education teachers at public institutions and understanding, from the perspective of the teachers, whether these courses reach the entirety of the teaching praxis. Since the perspective of teachers from seven municipalities in the State of Goiás, the general objective was to know the continuous education courses offered to Childhood Education teachers, analyzing whether they have been effectively contributing to the constitution of a critical and emancipatory teaching practice. For this, the following specific objectives were listed: to know and analyze the scientific-academic production that deals with the continuous education of Childhood Education teachers; systematically analyze some legal documents about continuous education at national and state levels; to investigate the teachers' conceptions and perspectives on continuous education courses carried out after initial training, and to understand what are the formative processes, continued and experienced by Childhood Education teachers in public institutions. The investigation process was consolidated based on the method of historical-dialectical materialism, on the works of several Marxist authors, allowing a scientific and critical reading of material reality, as well as understanding the multifaceted aspects and links that constitute continuous education. The methodology was anchored on a qualitative perspective, with a theoretical-bibliographic survey step, a documental analysis of laws and guidelines and an empirical stage. In this, there was a participation of 101 teachers from seven municipalities in the State of Goiás. An online questionnaire on a social networking platform was used as a methodological instrument. The research notes showed that public policies for teacher training have advanced in order to regulate continuous training processes as a right linked to teaching. However, the contradictions of the historical context and the privatist character of education in neoliberal times did not allow effective and continued consolidation in training throughout the teaching career. It is understood that it is necessary public policies building for the teachers training, at the national and municipal levels, that meet the training specificities related to the education and care of children in the first stage of Basic Education.